Reducing Women’s Cancer Rates: Early Detection of Breast Cancer and Cervical Cancer Through Self-Breast Exams (SADARI) and Pap Smears in Pinrang Regency, South Sulawesi - Masadah, Rina; Nelwan, Berti Julian; Ham, Jonathan; Raharja, Siska Putri Wulandari; Gosal, Steffy Rebecca; Rauf, Syahrul (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2025)
Breast and cervical cancer constitute the two most prevalent cancer types globally, with a disproportionately high mortality rate among women. While cervical cancer ranks eighth in terms of incidence, it remains a significant public health concern. A common challenge is the community’s delay in seeking healthcare attributed to a dearth of information, consequently leading to delayed treatment. The Pinrang Regency Health Department and the Family Empowerment and Welfare Team (TP-PKK) of South Sulawesi identified a high incidence of breast and cervical cancer among women in the Pinrang region. A primary obstacle to addressing this issue is the absence of public awareness regarding breast and cervical cancer, including early warning signs, symptoms, and associated risks. This problem is compounded by the district’s lack of an anatomical pathology specialist, hindering public education efforts and diagnostic capabilities. The objective of this activity was to enhance awareness of early detection for these two gynecological cancers in order to reduce mortality and morbidity rates associated with cancer. The method comprised an educational session on breast and cervical cancer, practicing SADARI, attended by 145 participants, followed by Pap smear tests for 45 volunteers. Program effectiveness was evaluated through pretest and posttest. A Wilcoxon signed-rank test was conducted to compare pretest and posttest scores. The results revealed a highly significant increase in scores p = 0.000 (p<0.005), suggesting that the educational program was successful in improving participants’ knowledge. A significant proportion of participants (57.8%) reported undergoing a Pap smear for the first time, highlighting the need for enhanced awareness and knowledge-sharing efforts regarding early detection of cervical cancer. The Pinrang Regency Health Department and TP-PKK provided essential support and participation. The Institute for Research and Community Service (LPPM) funds this community service project. The project was executed under contract number 0031/UN.4.22/PM.01.01.2024.